Time Course of Inflammatory and Procoagulant Markers in the Early Period After Total Hip Replacement. (1st February 2021) - Poredos, Peter; Poredos, Pavel; Jezovnik, Mateja K.; Mavric, Ana; Leben, Lara; Mijovski, Mojca Bozic; Maia, Paula; Haddad, Sandra; Fareed, Jawed
Our study aimed to investigate the levels and time-course of systemic inflammatory and hemostasis markers in the early postoperative period in patients undergoing total hip replacement (THR). The study included 70 patients of both sexes, average age 68.4 ± 10.9 years. Levels of inflammatory and hemostasis markers were measured before surgery (POD 0), a day after the surgery (POD 1) and 5 days after surgery (POD 5). In the postoperative period inflammatory markers increased. The operation provoked a significant increase of CRP on POD 1 in comparison to POD 0 (68.5 ± 5.4 vs 6.8 ± 2.2 μg/mL, p < 0.001) and the additional increase was registered on POD 5 (87.5 ± 8.1 vs 68.5 ± 5.4 μg/mL, p < 0.001). Interleukin-6 significantly increased on POD 1 (251.5 ± 21.6 vs 14.6 ± 7.1 μg/mL, p < 0.001) and after that (POD 5) decreased. After surgery leukocyte count, neutrophil/lymphocyte ratio and platelet/lymphocyte ratio were significantly higher compared to POD 0. Activation of coagulation in the postoperative period was shown by increased peak thrombin on POD 5 in comparison to POD 0 (185 ± 27 vs. 124 ± 31 nM, p < 0.001). D-dimer was increased on POD 1 and an additional rise was observed on POD 5. vWF also progressively increased in the observed period. Results of our study showed that after THR systemic inflammatory markers increased and coagulation function was enhanced. Determination of inflammatory and procoagulant markers could help identify patients at risk for cardiovascular thromboembolic events.